(untitled) (Eurasian Research Bulletin, 2021)
Many kinds of terms are used to express stable expressions in linguistics. This is due to the complexity of the nature of these stable compounds. The semantic, structural, and functional aspects of these terms are also quite complex. Accordingly, we can say that phraseologies are grouped together on the basis of structural-semantic, stylistic, complex and syntactic function in compound sentences and other principles.